Effects of OxyR regulator on oxidative stress, Apx toxin secretion and virulence of Actinobacillus pleuropneumoniae - Guo, Fangfang; Quan, Rong; Cui, Yifang; Cao, Xiaoya; Wen, Tong; Xu, Fuzhou (Frontiers in Cellular and Infection Microbiology, 2024)
Actinobacillus pleuropneumoniae is the causative agent of porcine pleuropneumonia, which has a high prevalence and mortality rate and can result in significant economic losses globally. The ability of A. pleuropneumoniae to defend itself against reactive oxygen species produced by host effector cells is a prerequisite for its survival. OxyR is a conserved bacterial transcription factor with a key role in oxidative stress response; however, little is known about its biological role in A. pleuropneumoniae. This study showed that OxyR is a conserved regulator and distributed in serovar 1-12 reference strains of A. pleuropneumoniae. The transcriptomic analysis of the oxyR disruption mutant indicated that OxyR is involved in multiple biological activities in A. pleuropneumoniae. We further demonstrated that inactivation of oxyR reduces urease activity, increases catalase expression, and promotes ApxI toxin secretion in A. pleuropneumoniae. And OxyR binding to the promoter of apxIBD explains the enhancement of ApxI toxin secretion. The oxyR disruption mutant had a lower adhesion and invasion abilities on porcine 3D4/21 and PT cells. Mice challenge experiment showed that inactivation of oxyR reduces virulence of A. pleuropneumoniae. Collectively, the results showed that OxyR plays an essential role in virulence of A. pleuropneumoniae.